The Fig - Ali Sarkhosh; Peter C. Andersen; Timothy E. Crocker (EDIS)
This 7-page fact sheet is a minor revision written by Ali Sarkhosh and Peter C. Andersen, and published by the Horticultural Sciences Department, October 2019.